PEMBELAJARAN MATEMATIKA MELALUI PENDEKATAN KONTEKSTUAL DENGAN GAYA BELAJAR VAK (VISUAL AUDITORY KINESTETIK) - Rahayu, Siti; Istiani, Ana (JURNAL e-DuMath, 2017)
Abstract:This research aims at finding out 1). To find out the average difference in learning outcomes of students learning mathematics using a contextual approach to the learningÂ  style VAK (Visual Auditory Kinesthetic) with a direct approach, 2). Knowing the average results of applied mathematics learning with contextual approach VAK learning styles (Visual Auditory Kinesthetic) higher than the average results of students mathematics learning approach is applied directly to the material of linear equations. The population of this study was all students in grade X MA Al-Hidayah. For data analysis was performed using the formula t-test for normally distributed samples.The conclusions of the research were as follows that the average results of students mathematics learning gained through the application of contextual learning style approach VAK (Visual Auditory Kinesthetic) higher than the average of students mathematics learning outcomes obtained through the direct approach.Keyword : Contextual approach, VAK (Visual Auditory Kinesthetic)